Pembuatan Gim Edukasi “PilahPilih” untuk Pemilahan Sampah Organik, Anorganik, dan B3 Berbasis Android - Andreas Evananda Gusti Purwanto; Paramaresthi Windriyani (UNIVERSITAS KALBIS, 2022)
The aim of this research is to develop PilahPilih, an educational game for sorting organic, inorganic and toxic and hazardous waste based on Android. The game is built using the Unity Game Engine. The programming language used is C#. The research method used is Game Development Life Cycle (GDLC). GDLC has several stages, starting from initiation, pre- production, production, testing, beta and release. The final result of this research is an educational game of sorting organic, inorganic and toxic and hazardous waste entitled PilahPilih. PilahPilih can be played on Android-based devices. The results of the PilahPilih game test were 94,1% of the 17 respondents became more aware of the types of waste after playing PilahPilih, in addition, as many as 88,2% of the total 17 respondents were motivated to carry out waste sorting independently after playing PilahPilih.